Membrane thinning for efficient CO2 capture. Issue 1 (31st December 2017) - Selyanchyn, Roman; Fujikawa, Shigenori
Abstract: Enhancing the fluxes in gas separation membranes is required for utilizing the membranes on a mass scale for CO2 capture. Membrane thinning is one of the most promising approaches to achieve high fluxes. In addition, sophisticated molecular transport across membranes can boost gas separation performance. In this review, we attempt to summarize the current state of CO2 separation membranes, especially from the viewpoint of thinning the selective layers and the membrane itself. The gas permeation behavior of membranes with ultimate thicknesses and their future directions are discussed. Abstract :